High-Flow Oxygen Therapy Concepts: Time to Standardize Nomenclature and Avoid Confusion. (May 2020) - Miller, David C.; Bime, Christian; Partharsarathy, Sairam; Mosier, Jarrod M.
High-flow nasal oxygen systems are rapidly being adopted as an initial noninvasive treatment for acute respiratory failure. However, the term "high-flow nasal cannula" is nonspecific and leads to imprecise communication between physicians, respiratory therapists, and nurses with the potential for patient harm. In this viewpoint and a brief review of the technology, we argue for a change in nomenclature in order to reduce the chance for future clinical, administrative, and research misunderstanding surrounding high-flow nasal oxygen systems.